2011
DOI: 10.1007/s12264-011-1032-6
|View full text |Cite
|
Sign up to set email alerts
|

Forced swimming stress does not affect monoamine levels and neurodegeneration in rats

Abstract: Objective The current study was aimed to investigate the correlations between immobility time in the forced swimming test (FST, a behavioral indicator of stress level) and hippocampal monoamine levels (markers of depression), plasma adrenalin level (a peripheral marker of stress) as well as fl uoro-jade C staining (a marker of neurodegeneration).Methods Male Sprague-Dawley rats were subjected to acute, sub-chronic (7 d) or chronic (14 d) FSTs and immobility time was recorded. Levels of noradrenalin, serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…It is well documented that any stress can elevate the level of adrenaline (22,23,24), regarding our results about levels of adrenaline after FST it can be seen that the control group showed lower values of adrenaline in the serum relative to the group that swam for 7 and 14 days, the average of adrenaline is slightly higher but there is no statistically significant differences found between these two groups, these data are in agreement with previous study (25), they concluded that in acute (7 days) and subacute (14 days) the levels of adrenaline after FST in rats didn't show significant increases of adrenaline compared with control group, this study revealed the importance of physical activity regarding neurodegeneration they stated that "14 days of FST stress didn't cause neuronal damage". Our results can indicate that acute stress-induced to rats was very stressful, Soria and colleagues reported the same data they confirmed high levels of adrenalin after acute physical stress (26). There were no statistically significant differences in the level of adrenaline in the serum between the group that was sleeping from day 14 of day 21 and the group that swam to 21 days, from these results we can conclude that the higher average of adrenaline level showed to be on day 14 of the experiment which are consistent with several studies (22,25).…”
Section: Disccusionsupporting
confidence: 83%
“…It is well documented that any stress can elevate the level of adrenaline (22,23,24), regarding our results about levels of adrenaline after FST it can be seen that the control group showed lower values of adrenaline in the serum relative to the group that swam for 7 and 14 days, the average of adrenaline is slightly higher but there is no statistically significant differences found between these two groups, these data are in agreement with previous study (25), they concluded that in acute (7 days) and subacute (14 days) the levels of adrenaline after FST in rats didn't show significant increases of adrenaline compared with control group, this study revealed the importance of physical activity regarding neurodegeneration they stated that "14 days of FST stress didn't cause neuronal damage". Our results can indicate that acute stress-induced to rats was very stressful, Soria and colleagues reported the same data they confirmed high levels of adrenalin after acute physical stress (26). There were no statistically significant differences in the level of adrenaline in the serum between the group that was sleeping from day 14 of day 21 and the group that swam to 21 days, from these results we can conclude that the higher average of adrenaline level showed to be on day 14 of the experiment which are consistent with several studies (22,25).…”
Section: Disccusionsupporting
confidence: 83%
“…In the prefrontal cortex, dopamine was increased by stressors like acute swim stress (H-FSS mice) or by acute restraint stress (Ahmad et al, 2012). Dopamine levels were also increased in the striatum of L-FSS mice, although in Sprague Dawley rats, striatal dopamine was unchanged or reduced by acute stress (Abbas et al, 2011; Ahmad et al, 2012). In addition, acute swim stress induced by the FSTv increased serotonin levels in the amygdala, hypothalamus, and brainstem of the less fearful L-FSS mice, similar to the elevation seen in the prefrontal cortex, striatum, and/or hippocampus of rats following acute swim stress or restraint (Abbas et al, 2011; Ahmad et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Dopamine levels were also increased in the striatum of L-FSS mice, although in Sprague Dawley rats, striatal dopamine was unchanged or reduced by acute stress (Abbas et al, 2011; Ahmad et al, 2012). In addition, acute swim stress induced by the FSTv increased serotonin levels in the amygdala, hypothalamus, and brainstem of the less fearful L-FSS mice, similar to the elevation seen in the prefrontal cortex, striatum, and/or hippocampus of rats following acute swim stress or restraint (Abbas et al, 2011; Ahmad et al, 2012). Furthermore, adult rats exposed postnatally to maternal separation showed a blunted dopamine and serotonin response to acute restraint stress in the striatum and brainstem, like our fearful H-FSS mice, but their basal brain monoamine levels were unchanged or slightly reduced (Jahng et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…However, the adult predominantly post mitotic brain does not need such homeostatic manipulation of the PSD-95 gene. In this regard, the decisive role of strong homeostasis in brain has been reported earlier (Abbas et al, 2012, Abbas et al, 2011. However, further work is required to delineate this explanation.…”
Section: Discussionmentioning
confidence: 58%